2021
DOI: 10.1177/17543371211039632
|View full text |Cite
|
Sign up to set email alerts
|

Using an overhead target increases volleyball-specific vertical jump performance

Abstract: In volleyball, spikes, and block jumps are among the most important movements when earning points and impacting performance. Many studies have found a greater jump height after acutely augmented feedback and extrinsic focus of attention on vertical jump height. However, there are limited studies on the long-term effects of using an overhead target on volleyball-specific vertical jumps (block and spike jumps). Therefore, the aim of the current study was to investigate the effects of using an overhead target on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
3
1
Order By: Relevance
“…In particular, the training with OG brought better results; however, the absolute difference between groups was small, i.e., 0.5 cm in the OG condition and 0.3 cm in the non-OG condition. In addition, the values we found are much lower than those reported by Makaruk et al (24) and Yildiz et al (44). In those studies, the absolute gain of groups training with OG over groups trained without OG was 3 cm in CMJ and about 4.5 cm in block jumps (volleyball), respectively.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…In particular, the training with OG brought better results; however, the absolute difference between groups was small, i.e., 0.5 cm in the OG condition and 0.3 cm in the non-OG condition. In addition, the values we found are much lower than those reported by Makaruk et al (24) and Yildiz et al (44). In those studies, the absolute gain of groups training with OG over groups trained without OG was 3 cm in CMJ and about 4.5 cm in block jumps (volleyball), respectively.…”
Section: Discussioncontrasting
confidence: 93%
“…Previous studies performed by Yildiz et al (44) and Makaruk et al (24) showed that plyometric training consisting of a series of various types of jumps with OG improved jump height to a greater extent than the same training performed without OG. In particular, after 5 weeks of intervention, professional volleyball players increased their spike and block jump height by about 12-15% when trained with OG and merely by 5% when trained without OG (44). Similarly, greater CMJ jump heights were found in a group who was instructed to touch the OG (gain of 12.8%) during practice than a group who was instructed to "jump as high as possible" (5.6%) or "reach their finger as high as possible" (5.4%) (24).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Furthermore, in reviewing the training concepts, methods, and techniques most frequently highlighted in these studies, some of the concepts that received attention include "Vertical Jump", which emphasises the importance of vertical jumping ability in various aspects of the game, such as attacks and blocks (Chaturvedi et al, 2023;Sotiropoulos et al, 2023;Yildiz et al, 2023). "Biomechanics" highlights the role of biomechanical analysis in the understanding of technique and player performance (Idrees et al, 2022;Sudds et al, 2023).…”
Section: Countrymentioning
confidence: 99%